Systematic review and classification of: Psychological first aid (2. ed.) - Rasmussen, Lene-Mari Potulski; Neumer, Simon-Peter (Ungsinn. Journal of Effective Interventions for Children and Adolescents, 2020)
Background: This article is a summary of the current knowledge regarding the intervention “Psykologisk førstehjelp”. It is a revision of the previous review of the same intervention (Neumer & Eng, 2013), and updated according to the new classification system and guidelines in Ungsinn (Martinussen et al., 2019). Psykologisk førstehjelp (PF) is primarily a first aid kit for children and adolescents (8-18 years), where the main goal is to prevent psychological difficulties by using the kit as self-help to deal with difficult emotions and situations. Method: The following databases were searched to find articles about the intervention: Embase, Medline and Psycinfo, NORART Cochrane, Cristin, NORA, SCOPUS and SweMed, NREPP, NICE and Blueprint. Information from the intervention developer has also been collected. Results: The results in this review includes information regarding the quality of the description, relevant studies and implementation quality. PF is a simple, but relatively well described intervention, with a pamphlet included in all of the first aid kits with information on how to use the intervention. The information guide also provides information about the most important elements to consider when using PF in the first line services. The intervention is built upon a solid theoretical foundation from cognitive behavioral therapy. The literature search did not result in any studies investigating the effect of the intervention as it is described to be used. According to Ungsinn criteria’s, the implementation quality of the intervention is marginally ensured, and it could be questioned whether the intervention is delivered as intended by all those practicing it. Conclusion: The intervention appears very user-friendly given the specific tools (figures and “helping hand”), and seems to appeal to the different mental health services and professionals working with children and adolescents. To claim that the intervention is effective there is a need for more studies with good methodological quality. Implementation quality should also receive more focus in the future. Psykologisk førstehjelp is classified at evidence level 2 – Theoretically grounded interventions.